Moral leadership and corporate social responsibility to clean up vice in Villa de Leyva - Osland, Asbjorn, (SAGE Knowledge. Cases., 2018)
The City of Villa de Leyva, California, was confronted with an explosion of erotic massage parlors. The police force was too stretched to deal with vice so the police chief opted to largely ignore it; only a few officers worked on vice. The City Council had to decide how to proceed. To date, there was no evidence of human trafficking. Still, there were other concerns. For instance, the rental spaces vacated after closing an illicit massage parlor sometimes remained vacant for a year or more, adding to urban blight. The City Council was entrusted with moral leadership: in addition to administering the laws of the state and city, its corporate social responsibility was to do the right thing for the various stakeholders in the city, including those engaged in the massage industry. The Councilman of District 3 suggested that the city sharpen its focus on licensure as a way to control the growth of the illegal massage industry and, eventually, to shut it down. When the massage parlors renewed business licenses annually the owners were expected to demonstrate that they were in compliance with assorted regulations; massage therapists in California had to pass a certification examination as part of this compliance, yet hardly any of the masseuses had done so. The Council agreed that whittling away at the problem by closing the noncompliant parlors and gradually choking others out bureaucratically was one option, but, some pointed out, it would take years because not all the parlors come up for renewal at the same time. Was there some other creative solution not yet foreseen - something that would take the various stakeholders into account: local government; law enforcement; community residents and business owners; the masseuses themselves; the owners of spas; the owners of rental property; professional organizations and certifying bodies such as the California Massage Therapy Council; and others?